Who should Decide for the Unrepresented?. (26th August 2015) - Courtwright, Andrew; Rubin, Emily
Abstract: Unrepresented patients lack the capacity to make medical decisions for themselves, have no clear documentation of preferences for medical treatment, and have no surrogate decision maker or obvious candidate for that role. There is no consensus about who should serve as the decision maker for these patients, particularly regarding whether to continue or to limit life‐sustaining treatment. Several authors have argued that ethics committees should play this role rather than the patient's treating physician, a common current default. We argue that concerns about the adequacy of physicians as surrogates are either empirically unfounded or apply equally to ethics committees. We suggest that physicians should be the primary decision maker for the unrepresented because of their fiduciary duties toward their patients. As part of the process of fulfilling these duties, they should seek the advice of third parties such as ethic committees; but final end‐of‐life decision‐making for the unrepresented should rest with the treating physician.